Glycemic variability and reference percentiles in very low birth weight preterm infants using continuous glucose monitoring - Irene Gutiérrez-Rosa; Manuel Lubián-Gutiérrez; Carmen Rodríguez-Barrios; Simón Pedro Lubián-López; Isabel Benavente-Fernández (PLoS ONE, 2026)
Glycemic control in very-low-birth-weight preterm infants is challenging due to the immaturity of glucose homeostasis during the early postnatal period. The first two weeks of life represent a critical window of metabolic adaptation, characterized by high variability and gradual stabilization of glucose levels; continuous monitoring during this period is therefore essential to capture clinically relevant trends. We aimed to describe daily glucose patterns and variability during the first 14 days and to generate gestational-age–specific reference percentiles for clinically stable preterm infants. A prospective observational study was conducted in a tertiary neonatal intensive care unit (2021–2024), with continuous glucose monitoring during the first 14 days of life. Of 203 eligible infants, 103 clinically stable preterm infants without major comorbidities were included and classified into three gestational age groups (24–26, 27–29, and 30–32 weeks). The median number of glucose readings per infant was 2,557 [1,681–2,959]. Mean glucose concentrations declined over the first two weeks in all groups, with the largest decrease during the initial 72 hours. Infants born at 24–26 weeks had higher mean glucose on day 1 (156.5 ± 47.2 mg/dL) and day 14 (121.4 ± 21.8 mg/dL), and greater variability than those born at 27–29 and 30–32 weeks. Reference percentiles reflected these differences: on day 1, the fifth to ninety-fifth percentiles were 92–245 mg/dL for 24–26 weeks, 65–168 mg/dL for 27–29 weeks, and 67–148 mg/dL for 30–32 weeks; by day 14, they were 73–185, 67–150, and 58–136 mg/dL, respectively.In summary, glucose concentrations and variability decreased with postnatal age, and the least mature infants exhibited higher and more variable values. These gestational-age–specific reference percentiles, derived from continuous monitoring may support individualized glucose management in neonatal intensive care.